Perceived Risk, Convenience, and Value of Nepalese e-banking Users: Mediation with Service Quality - Gyawali, Santosh; Adhikari, Ujjwal (Butwal Campus Journal, 2025)
The ongoing transition of Nepalese banking from traditional to digital platforms can be encapsulated as the digital-driven evolution of banking. The COVID-19 pandemic significantly accelerated consumers' shift toward digital banking. Sustaining this momentum requires a strong focus on creating customer value, which is crucial for ensuring customer retention and promoting the broader adoption of digital platforms. The research aimed to examine the e-banking service value with e-banking service quality, convenience (transaction and access), and perceived risk (financial and performance risk). A causal study design and non-probability convenience sampling were used to gather primary data from 206 e-banking users in the Kapilvastu district through a closed-ended, structured questionnaire survey. There was significant partial mediation of perceived service quality between perceived risk, convenience, and perceived value among e-banking users. The study implies a unique contribution to academia by exploring the dimensional impact of perceived risk and convenience on service quality and value perception from the perspective of customers. The study shows the practical direction toward maintaining the perceived customer value via the service quality of e-banking.